Pengaruh Literasi Digital Terhadap Kemampuan Evaluasi Kredibilitas Sumber Informasi dalam Menghadapi Hoax pada Mahasiswa - Annisa Maharani; Amara Putri Parisa; Faisyal Rahman Alfarizy; Muhammad Syafiq Ardyan (Indo Publishing, 2026)
In the digital era, information flows rapidly via the internet; however, this convenience brings significant negative consequences, such as the easy spread of fake news or hoaxes. The dissemination of hoaxes influences the perspectives and mindsets of the public, particularly university students. Recognizing this phenomenon, the government has positioned literacy as a key pillar in curbing the spread of hoaxes. This study aims to determine the impact of digital literacy on students' ability to filter information and avoid becoming entangled in the cycle of hoaxes. The study employs a systematic literature review method with a deductive approach, examining relevant prior research. Data were collected through literature searches and reviews, then analyzed to synthesize findings on the topic. The results indicate that digital literacy significantly influences students' ability to evaluate the credibility of information sources. It is evident that students with strong digital literacy skills tend to filter information before sharing it.